Finite Element Analysis on Triangular Web Profile Steel Section with Opening: Effects of Torsion Behaviour - De’nan, Fatimah; Hashim, Nor Salwani; Lye, Chu Wei (Journal of Structural Monitoring and Built Environment, 2022)
In recent decades, there is a massive demand for steel sections that normally used in the construction of roads, railways, other infrastructures, appliances and buildings.This paper summarizes the torsion behaviour analysis for triangular web profile steel section with opening. Comparison on parametrical study is made between triangular web profiles steel sections without opening and triangular web profile steel section with opening. A total of eighty finite elements analyses involve the changes of web thickness, flange thickness, span length, incremental loading, and size of circular opening were run to investigate the torsion behaviour effect on web opening shapes. The value of displacement and torsional rotation are the outcome of the final results. It was observed that triangular web profile steel section without web opening are able to maintain the static equilibrium by having higher torsional resistance compared to that of section with web opening.